Healthcare Failure Mode and Effect Analysis (HFMEA) as an Effective Mechanism in Preventing Infection Caused by Accompanying Caregivers During COVID-19—Experience of a City Medical Center in Taiwan. Issue 1 (January 2021) - Tiao, Chi-Hui; Tsai, Ling-Chin; Chen, Li-Chin; Liao, Yu-Mei; Sun, Li-Chen
Abstract : Background and Objectives: In response to the COVID-19 pandemic outbreak and to ensure the safety of epidemic prevention in the hospital, the hospital has established mitigation strategies in advance including risk assessment and effect analysis to control hospital visitors and accompanying persons. The study aims to assess the effectiveness of mitigation strategies implemented to effectively prevent the invasion and spread of the virus. Method: Conduct a status analysis in accordance with the Healthcare Failure Mode and Effect Analysis (HFMEA) 4-step model, construct a response workflow, confirm the failure mode and potential causes, perform hazard matrix analysis and decision tree analysis, and formulate risk control management measures. Results: For the 4 main processes and 9 subprocesses of the accompanying carers and contract caregivers entering the hospital, 26 potential failure modes and 42 potential causes of failure were analyzed. Following implementing improvement measures including strategies targeting the accompanying person, mitigation workflow failure rates decreased from 42 to 13 items, the pass rate for the maximum body temperature cutoff increased from 53.1% to 90.8%, and the compliance rate of hand washing increased from 89.5% to 100%. Conclusion: The HFMEA model can effectively implement preventive risk assessment and workflow management of high-risk medical procedures. The model can adjudicate the health of hospital visitors during the epidemic/pandemic, provide epidemic/pandemic education training and preventive measure health education guidance for hospital visits, and improve their epidemic prevention cognition. When combined, these strategies can prevent nosocomial infection to achieve the best anti-epidemic effect.